Investigating vancomycin dosing during a patient's transition from intermittent dosing to continuous infusion. (4th August 2018) - Sclater, Erin J. A.; Welch, Susan A.; Samios, Peter
Abstract: Aim: To investigate vancomycin dosing during the transition from intermittent dosing (ID) to continuous infusion (CI) in preparation for discharge on infuser bottles. Methods: Patients discharged with vancomycin infuser bottles (01/01/11 to 31/12/13) were identified from pharmacy dispensing software. Data including demographics, microbiology, dosing and plasma concentrations were analysed using Microsoft Excel. Dosing was compared against current guidelines. Results: Twenty patients had switched from ID to CI and were discharged on infuser bottles. At initiation of ID 65% (13/20) were started on total daily doses (TDD) that reflected guidelines. At the switch, 50% (10/20) were at steady state and 30% (6/20) were known to have therapeutic plasma concentrations. When switched to CI, 50% (10/20) were started on a dose that matched the TDD received during ID, while 30% (6/20) were switched to a lower — and 20% (4/20) to a higher — CI starting dose. At discharge 60% (12/20) of patients recorded therapeutic plasma concentrations; 30% (6/20) of patients remained on a CI dose that was equal to the TDD received prior to switching and 45% (9/20) had a decreased dose; while 25% (5/20) had their doses increased. Compared to current guidelines, 65% (13/20) were receiving a lower than recommended TDD. Patients stabilised on a CI for at least 72 h before discharge were less likely to require dose changes post‐discharge. Conclusion: The TDD recommended in current guidelines for ID may not reflect the patients' needs when prescribing a CI. Lower than recommended doses are more often required. Stabilising CI dosing prior to discharge can improve outpatient treatment by reducing post‐discharge dosage changes.